The Role of Medan City Legislative Candidates in Increasing the Mass Base in the 2024 Election (Case Study of DPD PKS Medan City) - Halim, Farid Muhammad; Situmorang, Tony P.; Warjio, Warjio (PERSPEKTIF, 2025)
This article aims to analyze the role of candidates for legislative members of the Prosperous Justice Party (PKS) of Medan City in increasing the mass base in the 2024 General Election. This study uses a qualitative approach with data collection methods through observation, in-depth interviews, and documentation studies. The primary data sources come from PKS legislative candidates, party members, and the people of Medan City. Data analysis was carried out qualitatively using role theory in organizations, according to Soerjono Soekanto, to describe the strategies used by legislative candidates to attract support. The study results show that PKS legislative candidates who actively interact directly with the community through gathering and holding social activities in mosques have increased the Party's mass base. This approach allows legislative candidates to understand the community's needs and aspirations better, which improves trust and support for PKS in the 2024 elections. This study concludes that active roles and social relationship-based strategies in the field are key factors in winning community support at the local level.